PENERAPAN ASUHAN KEPERAWATAN PADA PASIEN NY “D” DENGAN DIABETES MELITUS TIPE 2 DALAM PEMENUHAN KEBUTUHAN NUTRISI DI RSUD LABUANG BAJI MAKASSAR - Rahmawati - Rahmawati (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2020)
ABSTRACT According to WHO, 70% of total deaths in the world, 90-95% of cases are Type 2 Diabetes (T2D), most of which can be prevented by improving lifestyle. Type 2 Diabetes sufferers in Southeast Asia increased by 84%, namely 82 million people and it seems to have increased to 151 million people in 2045. The prevalence of T2D in Indonesia increased from 6.9% in 2013 to 8.5% in 2018, who are at risk of heart attack, stroke, blindness, kidney failure and death. This is due to lifestyle. Several studies have shown that T2D can prevent healthy eating patterns and dietary adjustments to maintain blood sugar levels. This study aims to describe nursing care in the patient Mrs.